Navigating the winds of change: strategic foresight and the power of weak signals - Jason Jabbour; Debra J. Davidson; Henrik Carlsen; Nicholas King; Simone Lucatello; Salvatore Aricò; Fang Lee Cooke; Ranjan Datta; Sir Peter Gluckman; Edgar E. Gutierrez-Espeleta; Andrea Hinwood; Gensuo Jia; et al. (Sustainability Science, 2026)
In an era of increased complexity, interdependence, uncertainty and rapidly advancing technology, the ability to identify and swiftly adapt to current and future trends is key to progressing sustainability. Intersecting drivers and stressors are converging to destabilize socioecological systems and reshape national, regional and global outlooks. The intersecting and converging crises of the 21st century have exposed the limits of planning that relies too heavily on linear extrapolations from well-known global/mega-trends. This study explores whether a limited number of emerging trends that only manifest as weak signals today serve as central conduits (super-nodes) for amplifying and accelerating systemic disruption. Using an exploratory mixed-methods design, a global Delphi survey (N = 790, 132 countries) generated 1200 horizon-scan items, inductively coded into 29 clusters. Scenario stress-testing distilled the findings into 280 candidate weak signals—ranked by likelihood, impact, and timing—from which 20 were shortlisted and mapped onto a 20 × 20 influence matrix through structured expert debate. Weighted degree centralities and a 10,000-run bootstrap test identified statistically significant hubs. Results suggest that anticipatory governance can be strengthened by prioritizing high-centrality signals and institutionalizing ongoing weak-signal scanning alongside transparent, multi-source decision-making to avoid cascading risks across planetary-health, economic, and technological systems. At the midpoint of a decade dominated by disruption–climate change, pandemic, geopolitical upheaval, widening inequality, war, misinformation and the rapid rise of Artificial Intelligence–we posit that strategic foresight and informed anticipation is a critical imperative in the pursuit of a global common good and a resilient future.
Keywords: Delphi Technique in Research; Sustainability and Climate Change Governance; Innovation, Sustainability, Human-Machine Systems